Control of human parasitic diseases - Molyneux, D. H. (Amsterdam ; London : Academic Press, 2006)
This volumes reviews state-of-the-art methods and historic successes of disease control.
Control of human parasitic diseases: context and overview / David H. Molyneux -- Malaria chemotherapy / Peter Winstanley, Stephen Ward -- Insecticide-treated nets / Jenny Hil, Jo Lines, Mark Rowland -- Control of Chagas disease / Yoichi Yamagata, Jun Nakagawa -- Human African trypanosomiasis: epidemiology and control / E.M. F{u1976}re, K. Picozzi, J. Jannin, S.C. Welburn, I. Maudlin -- Chemotherapy in the treatment and control of leishmaniasis -- Jorge Alvar, Simon Croft, Piero Olliaro -- Dracunculiasis (Guinea worm disease) eradication / Ernesto Ruiz-Tiben, Donald R. Hopkins -- Intervention for the control of soil-transmitted helminthiasis in the community / Marco Albonico, Antonio Montresor, D.W.T. Crompton, Lorenzo Savioli -- Control of onchocerciasis / Boakye A. Boatin, Frank O. Richards -- Lynmphatic filariasis: treatment, control and elimination / Eric A. Ottesen -- Control of cystic echinococcosis/hydatidosis: 1863-2002 / P.S. Craig, E. Larrieu -- Control of Taenia solium cysticercosis/taeniosis / Arve Lee Willingham, Dirk Engels -- Implementation of human schistosomiasis control: challenges and prospects / Alan Fenwick, David Rollinson, Vaughan Southgate.
Includes bibliographical references and index.
Print version record.
Elsevier
Keywords: Medical parasitology; Parasitic Diseases -- prevention & control; Parasitic diseases; Parasitology; MEDICAL -- Parasitology; Medical parasitology; Infectieziekten; Electronic books